The influence of pathogenetic therapy on the indicators of the quality of life of palliative patients with chemo resistant tuberculosis of lungs - Raznatovska, O. M.; Khudyakov, G. V.; Разнатовська, Олена Миколаївна (Запорізький державний медичний університет, 2018)
Background. According to the World Health Organization (WHO), Ukraine is on the list of countries in which there is a tuberculosis epidemic, and the effectiveness of treatment for chemo-resistant tuberculosis (CRT) is one of the lowest in the world. When CRT can create conditions for the transfer of patients with palliative treatment. The main objective of palliative care for tuberculosis patients in the world is to improve the quality of life (QL) of these patients with pathogenetic and symptomatic means. Questionnaires have been developed to monitor QL, including the Medical Outcomes Study-Short Form (MOS) "SF-36 Health Status Survey", which has already been widely used in phthisiology. To date, one of the most common analgesics is paracetamol. The American Institute of Rheumatology recommends paracetamol as a first-line drug for mild to moderate pain. The Research Department of the European Association of Palliative Care in 2012 conducted a scientific evaluation of WHO recommendations based on the GRADE evidence-based scoring system and recommended paracetamol for pain relief primarily. After analyzing the literature sources, we found that there are no data on the effect of paracetamol on QL in palliative patients of CRT lungs. The purpose of this work was to assess the effect of paracetamol QL in patients with CRT of the lungs who are on palliative care, according to the MOS SF-36 questionnaire.
Keywords: тези доповідей